Modulation and characterization of wax-based olive oil organogels in view of their application in the food industry - Silva, Pedro Miguel Peixoto (2021)
Olive oil has recognized health benefits but lacks structural resilience to act in a similar fashion as do the typically used triglycerides (TAGs) when applied in food manufacturing. Therefore, olive oil structuring is critical to widening its use as a healthier alternative in spreadable products. Foreseeing the development of an application for the food industry, three types of natural waxes were used as organogelators, generating olive oil organogels with distinct properties. Retail-simulated storage conditions were used to mimic real-life industrial and commercial use. Organogel systems were evaluated according to their oxidation stability and textural and rheological properties. Textural and rheological parameters increased in response to increasing gelator concentration, while oxidation values (below 1.5 meq O2·kg−1) remained within legal limits. Organogels displayed similar textural properties to those of commercially available spreadable products, while displaying a low critical gelation concentration. In short, it was shown that tailoring the physicochemical properties of organogels towards specific applications is possible. The produced organogels showed similar properties to the ones of commercially available spreadable products, revealing favourable oxidative profiles. Therefore, an industrial application can be easily foreseen, building on the natural characteristics of olive oil as a healthier alternative to current spreadable products.